2005
DOI: 10.1120/jacmp.v6i4.2137
|View full text |Cite
|
Sign up to set email alerts
|

Target localization for post‐prostatectomy patients using CT and ultrasound image guidance

Abstract: We conducted a study comparing B‐mode acquisition and targeting (BAT) ultrasound alignments based on CT data in the postoperative setting. CT scans were obtained with a Primatom CT‐on‐rails on nine patients. Two CT scans were obtained each week, while setup error was minimized by BAT ultrasounds. For the first three patients, a direct comparison was performed. For the next six patients, a template based on the shifts from the week 1 CT during treatment was used for subsequent setup. Comparison of isocenter shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…The mean movement calculated in this study is similar to that shown in previous studies . Table shows the mean magnitude and standard deviations of the prostate bed motion calculated by other groups who have also used CBCT imaging .…”
Section: Discussionsupporting
confidence: 86%
“…The mean movement calculated in this study is similar to that shown in previous studies . Table shows the mean magnitude and standard deviations of the prostate bed motion calculated by other groups who have also used CBCT imaging .…”
Section: Discussionsupporting
confidence: 86%
“…Despite the increasing popularity of image guided techniques for the intact prostate cancer patient, few studies are specifically relevant to the post‐prostatectomy patient. Paskalev et al demonstrated that ultrasound localization may be limited in its ability to accurately define the treatment volume 9 . Schiffner et al , using electronic portal imaging and implanted fiducial markers noted set‐up errors could be corrected using their on‐line technique 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have used ultrasound, megavoltage CT, kilovoltage (kV) CT imaging and implanted fiducial marker techniques to determine movement of the prostate bed, target volume, bladder and rectum 8–14 . Techniques for correcting patient position relative to soft tissue position are described only for the ultrasound imaging techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigators have published their experiences with various localization techniques, including conebeam CT (CBCT) (4), ultrasound (5,6), orthogonal imaging with alignment to surgical clips (7), or implanted gold seeds (8). While these studies have described the characteristics of inter-fractional displacement of the prostate bed relative to bony anatomy, there is as of yet, no detailed investigation of prostate bed movement during treatment delivery.…”
Section: Introductionmentioning
confidence: 99%